Pred vrati Sahare - Vovk, Ana (Geografski obzornik, 1996)
South of Sahara Tunisia begins with a peaty depression and continues to sandy deserts of Great Eastern Erg. Extreme climatic conditions affect all landscape elements and reflect especially as constant insufficiency of water, which is the most evident in Southern Tunisia, where Sahara clearly expresses its desert characteristics. The paper represents some other common attributes of presaharian Tunisia also
Keywords: fizična geografija; podnebje; relief; Sahara; Tunizija; voda